A Statistical Study of Nighttime Ionospheric NmF2 Enhancement at Middle‐to‐High Latitudes in the Northern Hemisphere. Issue 11 (23rd November 2022) - Zhao, Ling‐Xin; Zhang, Qing‐He; Xu, Tong; Xing, Zan‐Yang; Balan, N.; Wang, Yong; Ma, Yu‐Zhang; Gao, Dong‐Xing
Abstract: The electron density in the ionosphere usually continuously decreases during nighttime due to the vanishing of sunlit ionization. However, it sometimes increases unexpectedly, which has been called nighttime ionospheric enhancement. Previous researches studied this type of phenomenon mainly in the low‐to‐middle latitude regions. Here, we investigate the nighttime ionospheric NmF2 enhancement at middle‐to‐high latitudes in the northern hemisphere (NH) during solar cycles 23–24 by analyzing the ionosonde observations at Chilton (51.1°N, 359.4°E, geomagnetic 48.5°N), Juliusruh (54.6°N, 13.4°E, 51.7°N), Tromsø (69.9°N, 19.6°E, 66.9°N), and Qaanaaq (77.5°N, 290.8°E, 84.3°N), as well as comparing with the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM). The observations show that the nighttime NmF2 enhancement occurs mainly in the winter solstice months (November–February), and the occurrence rate and relative amplitude of the enhancement are inversely related to solar activity. The observed results are in good agreement with the results obtained from E‐CHAIM. Furthermore, the model shows the spatial distribution of the enhancement at the middle‐to‐high latitudes in NH in winter, most obvious in geomagnetic latitude between 50°N and 65°N, and have longitudinal minima centered at 30°W and maxima centered at 120°W and 75°E. From these results, this unique phenomenon at middle latitude is explained probably by the plasma flux from the higher altitudes (e.g., topside ionosphere and plasmasphere) diffusing downward into the ionospheric F2 layer. However, at polar regions, under the influence of the abundant high‐density structures such as polar cap patches, auroral blob, particle precipitation, etc., the F region plasma density enhancement becomes more complicated. Key Points: Nighttime NmF2 enhancement in the northern middle‐to‐high latitudes is statistically studied by using the observations and model Nighttime NmF2 enhancement depends significantly on season, solar activity, and spatial variations Plasma injection from the high altitudes above F2 layer possibly dominates the development of nighttime NmF2 enhancement at middle latitudes